Blockchain Adoption in Ireland's Financial Sector and its Regulatory Challenges and Implementation Opportunities - Gallagher, Fiona; O'Reilly, Aisling; Byrne, Ciarán (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This research explores the adoption of blockchain technology within Ireland’s financial sector, focusing on its implementation, challenges, and potential. The study adopts a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather data from a range of financial institutions and key stakeholders. A stratified sampling technique is used to select institutions based on size, including large multinational banks, mid-sized banks, and fintech startups. Purposive sampling targets key experts such as blockchain developers, regulatory bodies, and industry leaders for interviews. Surveys collect data on blockchain adoption levels, benefits, and challenges, while interviews provide deeper insights into the perspectives of stakeholders. The research findings reveal that blockchain adoption is still in its early stages but growing steadily, with larger multinational banks leading the way. Key benefits identified include enhanced transparency, security, and efficiency, while challenges include regulatory uncertainty, technological compatibility, and cybersecurity concerns. The study concludes that while blockchain holds transformative potential for Ireland’s financial sector, broader adoption is hindered by these barriers. Recommendations include increased collaboration between financial institutions, regulators, and blockchain developers, as well as clearer regulations to foster innovation while addressing security and compliance concerns.